Levels of ACL-straining activities increased in the six months prior to non-contact ACL injury in a retrospective survey: evidence consistent with ACL fatigue failure - Grodman, Louis H.; Beaulieu, Mélanie L.; Ashton-Miller, James A.; Wojtys, Edward M. (Frontiers in Physiology, 2023)
Recent evidence has emerged suggesting that a non-contact anterior cruciate ligament (ACL) tear can result from repetitive submaximal loading of the ligament. In other words, when the intensity of ACL-straining athletic activities is increased too rapidly, microdamage can accumulate in the ligament beyond the rate at which it can be repaired, thereby leading to material fatigue in the ligament and its eventual failure. The objective of this survey-based exploratory study was to retrospectively determine whether the levels of various athletic activities performed by ACL-injured patients significantly changed during the six months before injury. Forty-eight ACL-injured patients completed a survey to characterize their participation in various activities (weightlifting, sport-specific drills, running, jumping, cutting, pivoting/twisting, and decelerating) at three timepoints (one week, three months, six months) prior to ACL injury. Activity scores, which summarized the frequency and intensity of each activity, were calculated for each patient at each time interval. A series of linear mixed-effects regression models was used to test whether there was a significant change in levels of the various activities in the 6-month period leading up to ACL injury. Results showed that patients who sustained a non-contact ACL injury markedly increased their sport-specific drills activity levels in the time leading up to injury (p = 0.098), while those patients who sustained a contact ACL injury exhibited no change in this activity during the same time period (p = 0.829). Levels of running, jumping, cutting, pivoting/twisting, and decelerating increased for non-contact ACL-injured patients but decreased for contact ACL-injured patients, though not significantly (p values > 0.10). Weightlifting activity significantly decreased leading up to injury among contact ACL-injured patients (p = 0.002). We conclude that levels of ACL-straining athletic activities or maneuvers in non-contact ACL-injured patients markedly increased in the six months leading up to their injury, providing evidence that changing levels of certain activities or maneuvers may play a role in ACL injury risk. This warrants further investigation of the hypothesis that too rapid an increase in activities or maneuvers known to place large loads on the ACL can cause microdamage to accumulate in the ligament, thereby leading to failure.